Energy drink consumption among pre-clinical medical students attending a public medical school in Istanbul, Turkey - KULAK, ERCAN; KARAVUŞ, MELDA; LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: It has been reported that energy drink usage is increasing worldwide despite reports of severe adverse health effects. This study aimed to explore pre-clinical medical students' attitudes and perceptions in relation to energy drinks. Materials and Methods: This was a questionnaire-based descriptive study of pre-clinical medical students attending a public medical school in Istanbul, Turkey. Questions covered the students' sociodemographic characteristics, personal habits (e.g., smoking and alcohol consumption), energy drink perceptions and energy drink consumption, and their experience of side effects from energy drinks. Chi-square tests were used to compare the categorical data. Results: The mean age of the participants was 21.27 +/- 1.37 (range: 19-28) years, and 54.0% (n: 81) were females and 46.0% (n: 69) were males. Overall, 68.0% (n: 102) reported that they had consumed an energy drink at least once in their lives, with 29.4% of these reporting use in combination with alcohol, 22.6% reporting use before exams, 20.6% reporting use before a physical activity, 13.7% reporting use to relieve fatigue, and 48.0% reporting that they had only tried an energy drink out of curiosity. Conclusion: A large number of participants tried energy drinks out of curiosity, but energy drink consumption was quite common in combination with alcohol. Case studies are needed to provide detailed information on the actual adverse health effects of energy drinks, but in the meantime, energy drink consumption should not be encouraged. Health care providers should educate children and families for the adverse effects of energy drinks.
Keywords: Energy drinks; Alcoholic beverages; Medical students